The Effectiveness of 20% Moringa Leaf (Moringa oleifera Lam) peel-off Mask on Facial Skin Moisture - Nufuzi, Hayatun; Asrawati Sofyan (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2024)
Background: Indonesia’s tropical climate creates a variety of skin problems, including dry skin. The ingredients for making masks can come from nature such as moringahich have high antioxidants n moisturize facial skin. Purpose: To determine the effectiveness of 20% Moringa leaf (Moringa oleifera) peel-off mask on facial skin moisture. Methods: This research is a double-blind quasi-experimental method with a pre-post design. The sample used in this research is workers and students in the Tadulako University area. Result: Based on the Friedman test, the use of 20% concentration moringa leaf extract peel-off mask for improving skin moisture was not significantthe positive control and treatment, and dercreasing insignificantly in negative control groups (with p values of 0.484, 0.538 and 0.981, respectively). Based on the Wilcoxon test, it was found that thesults of skin moisture were not significant in the positive control, treatment and negative control groups from week 0 to week 2 (p= 0.301, p= 0.675, 0.916), week 2 to week 4 (p= 0.806, p= 0.53, p= 0.441), and week 0 to week 4 (p= 0.889, p= 0.529, p= 0.694). Conclusion: The 20% moringa leaf extract peel-off facial mask has potential effect to improve facial skin moisture, but not significant. The effect of 20% moringa leaf extract peel-off facial mask on facial moisture is still need to be investigated more.